Assist.Prof.Dr.Saad Muhammad Ali Hussein (Journal of the College of Basic Education, 2023)
The research follows the impact of Representative Izz al-Din al-Naqeeb in the debates of the Iraqi Council of Representatives in the period (1928-1958 AD), as he worked as a deputy in all electoral sessions during the research period except for the year 1937 AD, and he had a wide presence in discussing various economic, social and political issues in the sessions of the Iraqi Council of Representatives . The research material was distributed to an introduction and four topics that dealt with his family life, the early days of his career, and his views in the Parliament regarding the internal situation in Iraq, as well as his position on some Arab and international issues. The research reached several conclusions, the most important of which are: Representative Izz al-Din al-Naqeeb was one of the veteran deputies who worked in all electoral cycles, which enabled him to discuss various internal and external issues and express his opinions that were characterized by their agreement with the directions of the executive authority in most cases. Prejudice to people’s lives, such as the work of municipalities, fees, lands, public health, and agriculture. His proposals aimed at improving the economic and social situation of the citizen, and the deputy captain stood firmly in defense of the interests of the Iraqi people, especially the farmers affected by the border transgressions of neighboring countries as a result of reducing Iraq’s share of water in the tributaries of the Diyala River, Al-Naqeeb cared about Arab and international issues, especially issues of the Arab Maghreb and Syria, and Iraqi-American cooperation, and his discussions urged the Iraqi government to follow a policy supportive of Arab issues seriously and not be limited to statements and denunciations, and he believed in the importance of developing cooperation with the United States of America because of its important positive repercussions on Iraqi economy